Development of village-owned enterprise organizations (BUMDES) in North Minahasa regency, North Sulawesi province - Mardani Setiawan; Fernandes Simangunsong; Layla Kurniawati (Sean Institute, 2024)
The purpose of this research is to determine and analyze the Organizational Development of Village-Owned Enterprises (BUMDes), determine and analyze the supporting and inhibiting factors for the Organizational Development of Village-Owned Enterprises, as well as determine and analyze efforts to overcome the factors inhibiting the Organizational Development of Village-Owned Enterprises in Minahasa Regency North of North Sulawesi Province. The theory used as an analytical tool in writing this thesis is the theory from Gouillart and Kelly in Simangunsong (2014) which explains that Organizational Development requires 4 (four) stages (known as the 4 R model) for organizational renewal, namely